Knowledge and perception regarding pneumonia in children under five among parents at paediatric clinic in government hospital, Selangor (2021) - Japar, Salimah; Enoi, Sunnari; Abdul Raman, Rosna; Soh, Kim Geok; Ong, Swee Leong; Soh, Kim Lam (Wolters Kluwer - Medknow Publications and Media, 2021)
Background of study:In Malaysia, pneumonia had contributed to 6% of child death in 2010. Parents’ who have poor knowledge and perception toward childhood pneumonia will have a tendency to delay treatment seeking behaviour. Methods: A cross-sectional design with convenient sampling method was used in this study. The data were collected from March until April 2017 from 199 parents that broughttheir children for medical examination at the Paediatric Clinic. The data were collected using self-administered questionnaires. All data obtained were analysed using the Statistical Analysis Package for Social Sciences (SPSS) version 20 where descriptive analysis and chi-square test were used to present the results of the study. Results:The findings in this study showed that only 19.1% of the respondents have good knowledge while 55.3% have good perception regarding pneumonia in children under five. The findings indicated a significant relationship between the level of knowledge with family income, working sector, and number of children. A significant relationship was also found between the levels of perception with the level of education. Conclusion: The findingsin this study can be used to guide the health care team in planning appropriate intervention in order to improve the level of knowledge and perception regarding childhood pneumonia among parents. It can help the health care personnel to focus on the aspects that are not well understood by parents.